E.L., a modern-day Phineas Gage: Revisiting frontal lobe injury - de Freitas, Pedro H.M.; Monteiro, Ruy C.; Bertani, Raphael M.; Perret, Caio M.; Rodrigues, Pedro C.; Vicentini, Joana; de Morais, Tagore M. Gonzalez; Rozental, Stefano F.A.; Galvão, Gustavo F.; de Mattos, Fabricio; Vasconcelos, Fernando A.; Dorio, Ivan S.; et al. (Elsevier, 2022)
Background: How the prefrontal cortex (PFC) recovers its functionality following lesions remains a conundrum. Recent work has uncovered the importance of transient low-frequency oscillatory activity (LFO; < 4 Hz) for the recovery of an injured brain. We aimed to determine whether persistent cortical oscillatory dynamics contribute to brain capability to support ‘normal life’ following injury. Methods: In this 9-year prospective longitudinal study (08/2012-2021), we collected data from the patient E.L., a modern-day Phineas Gage, who suffered from lesions, impacting 11% of his total brain mass, to his right PFC and supplementary motor area after his skull was transfixed by an iron rod. A systematic evaluation of clinical, electrophysiologic, brain imaging, neuropsychological and behavioural testing were used to clarify the clinical significance of relationship between LFO discharge and executive dysfunctions and compare E.L.´s disorders to that attributed to Gage (1848), a landmark in the history of neurology and neuroscience. Findings: Selective recruitment of the non-injured left hemisphere during execution of unimanual right-hand movements resulted in the emergence of robust LFO, an EEG-detected marker for disconnection of brain areas, in the damaged right hemisphere. In contrast, recruitment of the damaged right hemisphere during contralateral hand movement, resulted in the co-activation of the left hemisphere and decreased right hemisphere LFO to levels of controls enabling performance, suggesting a target for neuromodulation. Similarly, transcranial magnetic stimulation (TMS), used to create a temporary virtual-lesion over E.L.’s healthy hemisphere, disrupted the modulation of contralateral LFO, disturbing behaviour and impairing executive function tasks. In contrast to Gage, reasoning, planning, working memory, social, sexual and family behaviours eluded clinical inspection by decreasing LFO in the delta frequency range during motor and executive functioning. Interpretation: Our study suggests that modulation of LFO dynamics is an important mechanism by which PFC accommodates neurological injuries, supporting the reports of Gage´s recovery, and represents an attractive target for therapeutic interventions. Funding: Fundação de Amparo Pesquisa Rio de Janeiro (FAPERJ), Universidade Federal do Rio de Janeiro (intramural), and Fiocruz/Ministery of Health (INOVA Fiocruz).
Keywords: Corpus callosum (C.C.); Low Frequency Oscillations; Magnetic Resonance Imaging (MRI); Neuropsychological tests; Phineas Gage; Prefrontal cortex (PFC); Transcranial Magnetic Stimulation; Traumatic brain injury (TBI)